Safety of routine childhood vaccine coadministration versus separate vaccination. Issue 9 (26th September 2022) - Bauwens, Jorgen; de Lusignan, Simon; Weldesselassie, Yonas Ghebremichael; Sherlock, Julian; Künzli, Nino; Bonhoeffer, Jan
Abstract : Introduction: As new vaccines are developed more vaccine coadministrations vaccines are being offered to make delivery more practical for health systems and patients. We compared the safety of coadministered vaccines with separate vaccination for 20 coadministrations by considering nine types of adverse events following immunisation (AEFI). Methods: Real-life immunisation and adverse event data for this observational cohort study were extracted from the Oxford-Royal College of General Practitioners Research and Surveillance Centre for children registered in the database between 2008 and 2018. We applied the self-controlled case series method to calculate relative incidence ratios (RIR) for AEFI. These RIRs compare the RI of AEFI following coadministration with the RI following separate administration of the same vaccines. Results: We assessed 3 518 047 adverse events and included 5 993 290 vaccine doses given to 958 591 children. 17% of AEFI occurred less and 11% more frequently following coadministration than would have been expected based on the RIs following separate vaccinations, while there was no significant difference for 72% of AEFI. We found amplifying interaction effects for AEFI after five coadministrations comprising three vaccines: for fever (RIR 1.93 (95% CI 1.63 to 2.29)), rash (RIR 1.49 (95% CI 1.29 to 1.74)), gastrointestinal events (RIR 1.31 (95% CI 1.14 to 1.49)) and respiratory events (RIR 1.27 (1.17–1.38)) following DTaP/IPV/Hib+MenC+ PCV; gastrointestinal events (RIR 1.65 (95% CI 1.35 to 2.02)) following DTaP/IPV/Hib+MenC+ RV; fever (RIR 1.44 (95% CI 1.09 to 1.90)) and respiratory events (RIR 1.40 (95% CI 1.25 to 1.57)) following DTaP/IPV/Hib+PCV+ RV; gastrointestinal (RIR 1.48 (95% CI 1.20 to 1.82)) and respiratory events (RIR 1.43 (95% CI 1.26 to 1.63)) following MMR+Hib/MenC+PCV; gastrointestinal events (RIR 1.68 (95% CI 1.07 to 2.64)) and general symptoms (RIR 11.83 (95% CI 1.28 to 109.01)) following MMR+MenC+PCV. Coadministration of MMR+PCV led to more fever (RIR 1.91 (95% CI 1.83 to 1.99)), neurological events (RIR 2.04 (95% CI 1.67 to 2.49)) and rash (RIR 1.06 (95% CI 1.01 to 1.11)) compared with separate administration, DTaP/IPV/Hib+MMR to more musculoskeletal events (RIR 3.56 (95% CI 1.21 to 10.50)) and MMR+MenC to more fever (RIR 1.58 (95% CI 1.37 to 1.82)). There was no indication that unscheduled coadministrations are less safe than scheduled coadministrations. Conclusion: Real-life RIRs of AEFI justify coadministering routine childhood vaccines according to the immunisation schedule. Further research into the severity of AEFI following coadministration is required for a complete understanding of the burden of these AEFI.